(untitled) (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted in the Tissue Culture Laboratory of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur-1706 from March 2013 to February 2014 for in vitro shoot regeneration of mint using different explants and levels of benzylaminopurine (BAP) in full strength MS media. Three different types of explants viz. nodal segment, shoot tip and leaf were evaluated using three levels of BAP (1.0, 2.0 and 3.0 mg/l) along with control for shoot regeneration. Results revealed that shoot tip and nodal segments performed better than leaf as explants in almost all the characters studied. Shoot tip and nodal segments initiated shoot within the shortest time of 9.6 and 10.6 days, respectively with 1.0 mg/l of BAP. Regarding number of shoot per explant and number of node/shoot, shoot tip and nodal segments along with 1.0 mg/l of BAP performed superior at almost all days after inoculation. In case of interaction of explants and BAP, better performance was recorded in most of the studied parameters from shoot tip and nodal segments alongwith 1.0 mg/l BAP. Therefore, for in vitro shoot regeneration of mint, shoot tip or nodal segment may be used with 1.0 mg/l of BAP. Bangladesh J. Agril. Res. 43(4): 703-716, December 2018